Detection of asymptomatic retinitis pigmentosa - Chiranjeev Singh Jhajj,; K Kalaivani,; B Saranya,; P Deepthika, (Indian Journal of Case Reports, 2021)
Retinitis pigmentosa (RP) is a heterogeneous group of progressive hereditary disorders that affect photoreceptors and retinal pigment epithelial function. It is one of the most common hereditary fundus dystrophies. We report the case of a 30-year-old female with RP, who presented to our outpatient department with a complaint of defective vision of both eyes for the past 2 years. Further detailed history revealed the presence of nyctalopia since childhood with a positive family history of nyctalopia in younger brother in a family of two sons and one daughter. It was followed by a complete ophthalmological workup in which the anterior segment examination was found to be normal and fundus examination revealed waxy pallor, arteriolar attenuation, and bony spicules in both eyes. Visual fields showed tubular fields in both eyes. Hence, a diagnosis of typical RP of both eyes was made which initially looked like a case of simple refractive error only. The patient was advised of family screening and 6 monthly follow-ups.